METHODOLOGY FOR THERMAL ANALYSIS OF COMBUSTION ENGINES, APPLIED TO AUTOMOBILES - AUCCAHUASI, WILVER (2024)
THE COMBUSTION ENGINES ARE WIDELY USED IN THE DAILY LIFE OF PEOPLE, IN CARS, WE FIND THEM WITH GREATER EMPHASIS, AND CURRENTLY HYBRID ENGINES AND ELECTRIC MOTORS ARE BEING USED. IN THIS ANALYSIS, ONE OF THE IMPORTANT FACTORS FOR THE FAILURE OF COMBUSTION ENGINES IS THE TEMPERATURE, FOR WHICH CARS HAVE COOLING SYSTEMS, THROUGH THE USE OF RADIATORS AND COOLANT-BASED SYSTEMS. IN THIS WORK WE PRESENT A METHODOLOGY FOR THE ANALYSIS OF THE STATE OF THE COMPONENTS OF THE COMBUSTION ENGINE SYSTEM IN CARS, THROUGH THE USE AND ANALYSIS OF THERMAL IMAGES, FOR WHICH IT IS NECESSARY TO IDENTIFY THE ZONES OR CONTROL POINTS DEPENDING ON THE MODEL AND TYPE OF ENGINE AND CAR, THE ANALYSIS PROCEDURE REQUIRES A THERMAL CAMERA, THE RESULTS PRESENTED ARE RELATED TO THE COMPARISON OF AN OPTICAL AND THERMAL IMAGE, IN ORDER TO LOCATE THE CONTROL POINT, THE METHOD CAN BE APPLIED BY MECHANICS, MAINTENANCE PERSONNEL AND CAR DRIVERS THEMSELVES, TO ANALYZE THE CONDITION OF THEIR CAR. © 2024 TRANS TECH PUBLICATIONS LTD, SWITZERLAND.